The Ethiopian Revolution - Tareke, Gebru (2009)
Revolution, civil wars, and guerilla warfare wracked Ethiopia during three turbulent decades at the end of the 20th century. Here, Tareke brings to life the leading personalities in the domestic political struggles, strategies of the warring parties international actors, and key battles.
Keywords: Eritrea